Intangible Investment and Low Inflation : A Framework and Some Evidence - Lall, Subir; Zeng, Li. (Washington, D.C. : International Monetary Fund, 2020)
Intangible investment is growing as a share of economic activity. We present a simple framework incorporating its distinguishing characteristic of generally greater scalability and lower marginal costs than tangible investment. We show evidence that this may have contributed to more elastic aggregate supply in recent years, which is consistent with lower inflation and a flattening of the Phillips curve. This framework also highlights the channels through which technological change, a large constituent of intangible investment, may be leading to wage stagnation and greater market concentration.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet